Development of Contextual Based Narrative Writing Module for Grade X Student of SMK - Putri Wulandari; Awani Manurung; Salamuddin Selian (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2019)
This study aims to describe the development of modules, validation of module development, and improve the learning outcomes of contextual based narrative writing. This research was conducted in class X SMK Ar-Rahman, Medan.The method used is a research and development method. Researchers use expert/expert validation and students to produce products and test the effectiveness of the product.The results obtained from this study: first, the development of contextual writing narrative essay writing modules is needed and appropriate by both teachers and students in the learning process.Second, the results of the validation carried out by experts / experts on the contextual writing narrative essay writing module are very good and worthy of being used as modules with an average percentage rating of 86% and are in the category of